2017
DOI: 10.29215/pecen.v1i2.453
|View full text |Cite
|
Sign up to set email alerts
|

Acidentes causados por aranhas e escorpiões no Estado do Ceará, Nordeste do Brasil: casos subnotificados e superestimados baseados na distribuição geográfica das espécies

Abstract: <p>A frequência dos acidentes causados por aracnídeos tem crescido ao longo dos anos e a maioria dos acidentes reportados não apresenta identificação das espécies causadoras, contribuindo assim para a subnotificação dos dados. No Estado do Ceará, informações específicas sobre acidentes com notificações completas ou descrição dos acidentes são escassos. No presente trabalho, os dados sobre acidentes com aranhas e escorpiões no Estado do Ceará do período de 2010 a 2015 foram confrontados com a distribuição… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
4
0
4
Order By: Relevance
“…The majority of cases reported were scorpion stings (164 cases, 70%), which is the most frequent at the national level 1,2 and also in studies conducted in other regions of the country 5,6,[11][12][13] . However, the mean incidence of cases of spider bites (12 cases) and scorpion stings (29.28) recorded per 100,000 inhabitants in this study for Cruzeiro do Sul is much higher than that reported for Brazil (2.9 and 16.7, respectively) and in the state of Acre (3.85 and 4.58) by Chippaux 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cases reported were scorpion stings (164 cases, 70%), which is the most frequent at the national level 1,2 and also in studies conducted in other regions of the country 5,6,[11][12][13] . However, the mean incidence of cases of spider bites (12 cases) and scorpion stings (29.28) recorded per 100,000 inhabitants in this study for Cruzeiro do Sul is much higher than that reported for Brazil (2.9 and 16.7, respectively) and in the state of Acre (3.85 and 4.58) by Chippaux 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Reversible kidney injury occurred in one of the cases and the most frequent complication was wound infection, in 6 cases. Two individuals were lost to follow-up, and the majority (19) were cured; a single case, which presented pyoderma gangrenosum, required amputation of the lower left limb.…”
Section: Research Notementioning
confidence: 99%
“… 1 , 14 - 18 However, underreporting and little epidemiological importance given to accidents involving venomous animals means that loxoscelism continues to be part of the group of neglected diseases. 18 , 19 , 21 , 24…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os escorpiões são animais terrestres com distribuição mundial, quase generalizada, podendo ser encontrados em desertos, savanas, cerrados, florestas tropicais, entre outros biomas, vivem frequentemente embaixo de folhas, pedras, madeiras, em fendas de rochas, entre tijolos ou quaisquer outros entulhos ou entre vegetações rasteiras e arbustos, habitam o planeta há milhões de anos, são encontrados em todos os continentes, com exceção da Antártida, sendo mais numerosos em ambientes áridos ou semiáridos. Em todo o mundo já foram registradas cerca de 2.239 espécies, com abrangência de 20 famílias e 165 gêneros (LOURENÇO;EICKSTEDT, 2009;AZEVEDO et al, 2017).…”
Section: Introductionunclassified